Recent progress of molecular diagnosis via CRISPR Cas-based biosensors and bioassays - Sophia Nazir (Talanta Open, 2023)
The immune systems of bacteria and archaea served as the inspiration for CRISPR/Cas technology, which won the 2020 Nobel Prize in Chemistry for its achievements in genetic manipulation. Because of its enormous value globally, molecular diagnostics emerged as a fresh wave of diagnostic technologies. A growing number of studies have demonstrated the compatibility of CRISPR/Cas technology with biosensors and bioassays for molecular diagnostics. As highly precise, sensitive, easily programmable, and device-independent sensors, CRISPR-based detection has received a lot of interest. One of the most precise and sensitive diagnostic techniques is nucleic acid-based detection. It has the potential for detecting other biomarkers, such as proteins and tiny compounds, with more study. This study provides insight into CRISPR-based biosensors and recent advancements from nucleic acids to other non-nucleic small molecules or analytes such as proteins and presents the challenges and perspectives of CRISPR biosensors and bioassays.